Aqueous humor penetration of topical bimatoprost 0.01% and bimatoprost 0.03% in rabbits: response to authors - Chang-Lin J-E (Dove Medical Press, 2011)
Joan-En Chang-Lin, Amy L Batoosingh, David A Hollander, Rhett M Schiffman, Diane D-S Tang-LiuAllergan, Inc, Irvine, CA, USAWe read with great interest the recent article by Ogundele and Jasek,1 in which the authors concluded that bimatoprost ophthalmic solution 0.01% (Lumigan®; Allergan, Inc, Irvine, CA) produced lower bimatoprost acid concentration than bimatoprost ophthalmic solution 0.03% (Lumigan; Allergan, Inc) in the aqueous humor of rabbits. This conclusion was made based on two treatment time points (30 and 90 minutes) with a small sample size (n = 4) at each time point and with large variability.